Application of Clean and Healthy Behavior Activities In the Covid-19 Pandemic in Miftahul Islamic Boarding School, South Jakarta, Indonesia - Mulyanti Mulyanti; Rina Yuliana Subur; Sri Rahayu (Placentum: Jurnal Ilmiah Kesehatan dan Aplikasinya, 2022)
Introduction: The COVID-19 pandemic has hit countries around the world, including Indonesia. One of the sectors affected by the COVID-19 pandemic is the education sector. Educational institution in Indonesia has designed a distance learning program to prevent COVID-19 but not all educational institutions can implement this, for example an Islamic boarding school. The Pandemic COVID-19 causes the weakness of teaching and learning activities in islamic boarding school. However, teaching and learning activities must continue to be carried out with study times, to follow government directives in preventing the wider spread of the pandemic COVID-19. One of the ways to prevent the spread of COVID-19 is to wash your hands with soap and running water, also maintaining clean and healthy behavior activities.Method: This study uses a qualitative method with a descriptive phenomenological approach. The sample was selected purposively, the research informants were student Islamic Boarding School Miftahul, South Jakarta and key informants consisted of boarding school leaders, teachers in the boarding school environment on November 2021.Result: The results showed that the informants had behaved in a clean and healthy life both as an effort to prevent the covid-19 virus.Conclusion: It is hoped that the board and management of Islamic boarding schools can coordinate with local health center health workers to conduct health education related to Clean and Healthy Behavior (PHBS).